2016
DOI: 10.3390/nu8120788
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Health Behaviours in Childhood on Attention Deficit and Hyperactivity Disorder in Adolescence

Abstract: Attention-deficit and hyperactivity disorder (ADHD) in children and adolescents is a global public health burden. Identification of health-related behavioral risk factors including diet quality and physical and sedentary activities for ADHD is important for prioritizing behavioral intervention strategies to improve mental health. This study aimed to examine the association of diet quality, physical activity, and sedentary behaviours in childhood with ADHD throughout adolescence. We linked data from grade five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
12
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 58 publications
5
12
1
1
Order By: Relevance
“…We observed that children who engaged in excessive use of computers and video games (≥3 vs. <1 h/day) had significantly more diagnoses of ADHDs, which is consistent with previous studies reporting that playing computers and video games was associated with increased attention problems and ADHD among children and adolescents (33,49,50). While some studies observed that increased time spent on playing computers and video games was related to more internalizing disorder problems such as depression and anxiety among youth (20, 51), we did not find a significant association between the use of computers and video games and internalizing disorder in children.…”
Section: Discussionsupporting
confidence: 91%
“…We observed that children who engaged in excessive use of computers and video games (≥3 vs. <1 h/day) had significantly more diagnoses of ADHDs, which is consistent with previous studies reporting that playing computers and video games was associated with increased attention problems and ADHD among children and adolescents (33,49,50). While some studies observed that increased time spent on playing computers and video games was related to more internalizing disorder problems such as depression and anxiety among youth (20, 51), we did not find a significant association between the use of computers and video games and internalizing disorder in children.…”
Section: Discussionsupporting
confidence: 91%
“…The results are in line with another study suggesting the association between ADHD and overweight was completely explained by cumulative psychosocial risks [19]. Prime candidate environmental factors that increase the risk for both ADHD and overweight and that are shared by family members include inadequate health behaviors, foremost poor nutritional habits and lack of physical activity [4851] as well as chronic stress [19]. Poor nutritional habits, lack of physical activity, and chronic stress tend to cluster with each other and within families [19], particularly in families with disadvantaged backgrounds [52].…”
Section: Discussionsupporting
confidence: 87%
“…Wu et al [24] concluded that health-promotion programs designed to improve the diet and increase the physical activity of children may mitigate their hyperactivity and inattention and consequently reduce the public health burden of ADHD. The LDK is one such nationwide program that allows children and adolescents from big cities and small towns to participate in physical activity and nutritional education as well as undergo regular athletic training.…”
Section: Discussionmentioning
confidence: 99%
“…In the mentioned study of Wu et al [24], the ADHD diagnosis was more common in individuals characterized by a lower quality of diet, lesser level of physical activity, and more screen time playing computer and video games. This observed association between physical activity and hyperactivity may be an outcome of the time spent playing computer and video games because, in general, when an individual spends a lot of time playing computer and video games, s/he does not spend this time on physical activity.…”
Section: Discussionmentioning
confidence: 99%